PERSEPSI WISATAWAN MANCANEGARA TERHADAP PROMOSI WISATA BUDAYA DAN SEJARAH DI YOGYAKARTA - Muhammad Khanif Panuntun Rizki; Yenni Sri Utami (Universitas Kristen Satya Wacana, 2018)
Yogyakarta, a city that is the most desirable destination for visits by foreign tourists from various parts of the world. Yogyakarta must be able to meet the desires of the foreign tourist market, especially in the promotion of cultural and historical tourism objects that are presented to tourists. This study aims to analyze the perceptions of foreign tourists towards the promotion of cultural and historical tourism in Yogyakarta, To improve the quality of objects associated with factors that influence foreign tourists to visit Yogyakarta, including events, attractions, facilities, infrastructure and services. To analyze and understand the perceptions of foreign tourists after a visit in order to know the desires of the foreign tourist market. The method used in this research was qualitative method. The data collection techniques were in-deep interviews, documentation, and archives. The theory which was used to analyze the foreigners’ perceptions was – Trial – Reinforcement (A-T-R). The results of this research showed that this research had not been tested correctly based on the expectation of Yogyakarta tourism element. There were negative perceptions from the foreigners because almost all of them had not gotten the promotion yet, especially from the website Visitingjogja.com although there were many contents and innovations. Those negative perceptions from the foreigners could be the reason for the tourism element to improve the promotion so that Yogyakarta can be known more and the foreigners can understand more when they visit Yogyakarta